Computation of stiffness and damping derivatives of an Ogive in a limiting case of mach number and specific heat ratio - Shabana, Aysha; Crasta, Asha; Khan, Sher Afghan; Aabid, Abdul; Baig, Muneer (Tech Science Press, 2022)
This work aims to compute stability derivatives in the Newtonian limit in pitch when the Mach number tends to infinity. In such conditions, these stability derivatives depend on the Ogive’s shape and not the Mach number. Generally, the Mach number independence principle becomes effective from M = 10 and above. The Ogive nose is obtained through a circular arc on the cone surface. Accordingly, the following arc slopes are considered λ = 5, 10, 15, −5, −10, and −15. It is found that the stability derivatives decrease due to the growth in λ from 5 to 15 and vice versa. For λ = 5 and 10, the damping derivative declines with an increase in λ from 5 to 10. Yet, for the damping derivatives, the minimum location remains at a pivot position, h = 0.75 for large values of λ. Hence, when λ = −15, the damping derivatives are independent of the cone angles for most pivot positions except in the early twenty percent of the leading edge.